2008
DOI: 10.1212/01.wnl.0000304134.33380.1e
|View full text |Cite
|
Sign up to set email alerts
|

Why do patients with PSP fall?

Abstract: Taken together, these results indicate that abnormal otolith-mediated reflexes may be at least partly responsible for frequent falls in progressive supranuclear palsy, and deserve further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 38 publications
(41 reference statements)
3
47
1
1
Order By: Relevance
“…In addition, Probst et al [22] reported presence of neurofibrillary fibers, neuropil threads throughout the basal ganglia and brainstem in PSP. In addition impairment of balance in PSP has been attributed to central vestibular dysfunction [9], deficits in motor programming [23], abnormal otolith-mediated reflexes [24], synergistic deterioration of brainstem and higher cortical functions [25] and involvement of cerebellum [26].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Probst et al [22] reported presence of neurofibrillary fibers, neuropil threads throughout the basal ganglia and brainstem in PSP. In addition impairment of balance in PSP has been attributed to central vestibular dysfunction [9], deficits in motor programming [23], abnormal otolith-mediated reflexes [24], synergistic deterioration of brainstem and higher cortical functions [25] and involvement of cerebellum [26].…”
Section: Discussionmentioning
confidence: 99%
“…The question is whether there is enhanced VCR activity per se (stabilising the head in space during body movements) or whether there is a loss of oppositely directed eye-head movements (which reset the eyes in the orbit and the head on the trunk). The former mechanism is unlikely because in PSP vestibular function is essentially normal [5,6], or even decreased according to the only study of PSP using VEMPs (although not in subjects specifically exhibiting torticollis) [7]. This is in sharp contrast to fast resetting eye and head movements, such as eye-head saccades and quick phases of nystagmus, notoriously reduced in PSP [3,5,8].…”
Section: Lettermentioning
confidence: 99%
“…When normal humans look through prisms to dissociate vergence angle from viewing distance, it is the latter that sets the magnitude of LVOR [3]. In some disorders with deficient or absent vergence responses, such as progressive supranuclear palsy (PSP), the magnitude of LVOR cannot be increased during near-viewing [20,21 ]. However, in other disorders such as cerebellar ataxias, the magnitude of LVOR is not increased even when the patient converges [22].…”
Section: Interaction Of Vergence With Other Eye Movementsmentioning
confidence: 99%